Analisis Pengaruh Kualitas Produk, Harga, Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi kasus pada Marketplace Shopee) - Wulandari, Zanualita; Mulyati, Awin; Tjahjono, Endro (Universitas 17 Agustus 1945 Surabaya, 2020)
This research is motivated by the growing development of online buying and selling in Indonesia so that companies or online buying and selling website platforms must develop strategies to improve product quality, price, and service quality. To provide customer satisfaction the company must provide good quality products, affordable prices, and fast and responsive service quality. The purpose of this study was to determine the magnitude of influence between product quality (X1), Price (X2), and service quality (X3) on consumer satisfaction (Y) in the Shopee marketplace. The research methodology used is quantitative research using survey methods. The sampling technique uses simple random sampling with 105 respondents. Data collection techniques using a questionnaire that was processed using SPSS version 16.0. The method of data analysis uses multiple linear regression analysis. The results showed that product quality had no partial effect on consumer satisfaction in the Shopee marketplace, this was evidenced by a tcount of 1.612 and a significance value of 0.110. Price has a partial effect on customer satisfaction in the Shopee marketplace, this is evidenced by the tcount of 4.030 and the significance value of 0,000. Service Quality has a partial effect on customer satisfaction in the Shopee marketplace, this is evidenced by the tcount of 4.594 and a significance value of 0,000. While based on the results of the simultaneous test statistical calculations, it can be concluded that product quality, price and service quality simultaneously influence consumer satisfaction in the Shopee marketplace, this is evidenced by the Fcount value of 45.452 and a significance value of 0,000 and a coefficient of determination of 0.574 which means that consumer satisfaction can be explained by product quality, price and service quality variables of 57.4%.Keywords: Product quality, Price, Service quality, Consumer satisfaction